Conceptual approaches for creating an information resource «Online monitoring system of the condition of the environment Orshi and Orshan district» - Germenchuk, Mariya G.; Zhuravkov, Vladzislav V.; Kononchuk, Tatyana P.; Shidlovskaya, Tatyana A.; Golovatiy, Sergey E.; Tonkonogov, Boris A. (Journal of the Belarusian State University. Ecology, 2020)
The article presents conceptual approaches to creating the information resource «System of online monitoring of the state of the environment components of the city of Orsha and the Orsha district». The work is carried out as part of the event «Creating a system for online monitoring of the state of the environment components of the city of Orsha and the Orsha district» of subprogram 5 «Ensuring the functioning, development and improvement of the National Environmental Monitoring System in the Republic of Belarus» of the State program «Environmental protection and sustainable use of natural resources» for 2016–2020, approved by the Decree of the Council of Ministers of the Republic of Belarus dated 03.17.2016 No. 205. As a result of the work, a Concept was developed on the basis of modern information systems, international best practices and with the choice of optimal solutions for the phased expansion of the information resource «System for online monitoring of the state of the environment components of the city of Orsha and Orsha district».